Parioglossus galzini, a new species of ptereleotrid dartfish from Rapa Island (Teleostei: Gobioidei: Ptereleotridae) - Williams, Jeffrey T.; Lecchini, David (Zootaxa, 2004)
A new species of dart fish, Parioglossus galzini sp. nov., is described based on specimens collected in Haurei Bay, Rapa Island (French Polynesia). It is distinguished from all other described species of Parioglossus as follows: dark lateral body stripe absent, 100 or more scales in longitudinal series from above pectoral-fin base to base of caudal fin, pectoral-fin rays 19 21, membrane of first dorsal fin attached to second dorsal fin in males and females, mature males with dorsal-fin spines 3 5 filamentous and about equal in length, fresh males with narrow yellow stripe running dorsolaterally along body from head to caudal fin.